Systematic total arch replacement with thoraflex hybrid graft in acute type A aortic dissection: A single centre experience - Chivasso, Pierpaolo; Mastrogiovanni, Generoso; Bruno, Vito Domenico; Miele, Mario; Colombino, Mario; Triggiani, Donato; Cafarelli, Francesco; Leone, Rocco; Rosapepe, Felice; De Martino, Matteo; Morena, Elvira; Iesu, Ivana; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction In the last two decades, a more aggressive approach has been encouraged to treat patients with acute type A aortic dissection (ATAAD), extending the repair to the aortic arch and proximal descending thoracic aorta with the frozen elephant trunk (FET) implantation. Here, we report our single-centre experience with the FET technique for the systematic treatment of emergency type A aortic dissection. Materials and methods Between December 2017 and January 2022, 69 consecutive patients were admitted with ATAAD; of those, 66 patients (62.9 ± 10.2 years of age, 81.8% men) underwent emergency hybrid aortic arch and FET repair with the multibranched Thoraflex hybrid graft and were enrolled in the study. Primary endpoints were 30 days- and in-hospital mortality. Secondary endpoints were postoperative morbidity and follow-up survival. To better clarify the impact of age on surgical outcomes, we have divided the study population into two groups: group A for patients <70 years of age (47 patients), and group B for patients ≥70 years (19 patients). Time-to-event analysis has been conducted using the Log-rank test and is displayed with Kaplan-Meier curves. A multiple Cox proportional Hazard model was developed to identify predictors of long-term survival with a stepwise backward/forward selection process. Results 30-days- and in-hospital mortality were 10.6 and 13.6%, respectively. Stroke occurred in three (4.5%) patients. Two (3.0%) patients experienced spinal cord ischemia. We did not find any statistically significant difference between the two groups in terms of main post-operative outcomes. The multivariable Cox proportional hazard model showed left ventricular ejection fraction (HR: 0.83, 95% CI: 0.79–0.92, p < 0.01), peripheral vascular disease (HR: 15.8, 95% CI: 3.9–62.9, p < 0.01), coronary malperfusion (HR: 0.10, 95% CI: 0.01–0.77, p =0.03), lower limbs malperfusion (HR: 5.1, 95% CI: 1.10–23.4, p = 0.04), and cardiopulmonary bypass time (HR: 1.02, 95% CI: 1–1.04, p = 0.01) as independent predictors of long term mortality. Conclusions Frozen elephant trunk repair to treat emergency type A aortic dissection appears to be associated with good early and mid-term clinical outcomes even in the elderly.